Pilihan Kata Dalam Buku Pegangan Bahasa Prancis Le Nouveau Taxi A1 Karya Capelle-Menard - Mohamad Syaefudin (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2020)
This study discusses archisémème in the book le nouveau taxi A1.  This study aims to (1) describe the form and meaning of archisémème contained in the book Le nouveau taxi A1, and (2) describe the use of archisémème in the book Le Nouveau Taxi A1. This research is a library research that uses data in the form of a phrase in the Le Nuveau Taxi A1 book.  A1.  Archisémème contained in the book Le nouveau taxi A1 is the object of this study.  Data was collected using the note note method.  Meanwhile, data analysis was carried out using the translational equivalent method.  The results of this study indicate that (1) there are 2 classes of archisémème words found in this study, namely: verbs, and adjectives.  Archisémème variation is still maintained as long as it can be understood by French learners;  (2) the use of archisémème contained in narrative texts and dialogues can help French learners to construct depictions of stories conveyed in daily communication activities by users of the book Le Nouveau Taxi A1.